Taxonomic notes on Australian species of Sciacharis (Magellanoconnus) (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2014)
Two species of Australian Cyrtoscydmini were placed in the subgenus Magellanoconnus Franz of Sciacharis Broun: S. carinifrons (Franz) and S. kangarouana (Franz) (both originally described in Neuraphoconnus, a junior synonym of Magellanoconnus Franz). Examination of type specimens revealed that these species names, published in the same paper, are synonymous and S. carinifrons is here selected as a valid name. This species is redescribed and its morphological details are illustrated. Possible relationships of Australian Magellanoconnus with Sciacharis s. str. and Euconnus s. str. are discussed.